MA’NAVIY-MA’RIFIY TADBIRLARNI O‘TKAZISHDA MULTIMEDIA VOSITALARINING AHAMIYATI (Modern education and development, 2025)
This article discusses the reforms being implemented in the process of spiritual and educational work, how to use modern technologies, and the types of modern technologies.